Age and gender disparities in administration of opioid for cardiac chest pain in the emergency department - Emad Awad; Heba Abushanab; Raed Darwish; Taryn Hunt-Smith; Mohamed Shubair; Jeffrey Druck (PLoS ONE, 2025)
Background Previous data have shown sex differences in pain management for patients with cardiac chest pain in the emergency department (ED); however, the joint effect of sex and age on opioid administration has not been well studied. This study aimed to evaluate the combined effect of age and sex on the administration of opioid analgesics, specifically morphine and fentanyl, in ED patients presenting with cardiac chest pain. Methods This retrospective observational study included adults aged 18 years and older who presented to a single tertiary academic ED with acute cardiac chest pain between 2021 and 2025. Patients were categorized into four age–sex groups: older women (>57 years), younger women (18–57 years), older men (>57 years), and younger men (18–57 years). The primary outcome was the administration of intravenous (IV) morphine or fentanyl during the ED visit. Multivariable logistic regression was used to examine the association between these groups and the administration of opioids. Findings Among 1,870 eligible patients, 474 (25.4%) were older women, 323 (17.3%) were younger women, 659 (35.2%) were older men, and 414 (22.1%) were younger men. Compared to older women, all other age–sex groups had higher odds of receiving IVmorphine. Younger men had the highest odds (OR 2.19; 95% CI: 1.58–3.04; p < 0.001), followed by older men (OR 1.99; 95% CI: 1.22–3.26; p = 0.006) and younger women (OR 1.48; 95% CI: 0.87–2.52; p = 0.15), although the latter was not statistically significant. IV fentanyl use was low overall and did not differ significantly between groups. Conclusions Older women were significantly less likely to receive IV morphine than men. These findings suggest the need for standardized pain protocols and targeted clinician education to reduce potential bias in ED pain management.